The whale watchers' guide - Gardner, Robert, 1929-2017.; Sineti, Don. (New York : J. Messner, 1984)
Discusses whales and whaling and explains how to tell one whale from another and how to watch them from land and sea.
Includes index.
Bibliography: page 165.
Keywords: Whales -- Juvenile literature; Wildlife watching -- Juvenile literature; Literature